Knowledge Society: Lofty Ideal, Money-Making Buzzword or the Genuinely Empowering Social Arrangement? - Srbljinović, Armano (Array, 2008)
The article considers the prospects of knowledge society from the viewpoint of Douglass C. North's five propositions about institutional change, which assert, in a nutshell, that the institutional change is brought about through the interplay of institutionally imposed constraints on interactions among social actors, in one direction, and the social actors' perceptions of opportunities that incrementally alter institutional constraints and rules, in the other direction. The analytical findings are further supported with insights in European knowledge society development provided by the recent Report of the European Commission's Expert Group on Science and Governance. The main conclusion is that the development of multiple, diverse, and decentralized civic 'knowledge-abilities' is necessary if the promise of knowledge society as a really empowering social arrangement is to be fulfilled.